Syrian Arab Republic : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
Syria faces two interrelated medium-term challenges posed by the prospective decline in its oil reserves. The recently approved five-year plan (FYP) laid down a comprehensive strategy to address these challenges. Syria's public finances are headed for challenging times in the coming 10-15 years. Large fiscal deficits have marked the economic history of many developed and developing countries alike during the 1970s and 1980s, with damaging consequences to their economies. Although financial markets can help keep the deficit bias in check, market discipline has proved mostly inadequate.